Creative Lanna Multimedia Archive Needs Assessment Among Media Industry Practitioners and Individual Users - Sukittanon, Siwaporn; Bunma, Weerapat (Journal of Communication and Integrated Media, 2024)
This study aims to investigate the usage needs of the Lanna Multimedia Archive among media industry practitioners and individual users. The research employs a survey method, utilizing online questionnaires developed from the Value Proposition framework. A specific sample group was selected, consisting of media industry practitioners at provincial, national, and international levels, and individual users with relevant work experience in media file usage. A total of 262 respondents participated in the survey. Findings indicate that individual users encountered challenges with the difficulty of file downloading processes and membership requirements on digital file distribution websites. Media industry users expressed difficulties in finding files that matched their needs and annoyance with platform advertisements. Both groups expressed a need for wide-angle images of significant Lanna locations, festival images, and rare historical images. Similarly, both groups indicated the needs of audio files of traditional Lanna music and Lanna musical instruments. The media practitioners also requested specific files quality. As a result, Lanna Multimedia Archive website developers should utilize these findings to enhance product and service offerings, ensuring a fit between the website and market demands (Product-Market Fit) and providing solutions that match consumer needs (Product-Solution Fit).